Investigating the Impact of Entrepreneurial Management on Entrepreneurial Competence: Emphasizing the Role of Entrepreneurial Behavior - Kafaee, Farzad; Hemadi, Sedigheh; Hoshmand, Ali (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: In the scope of the new millennium, examining entrepreneurial ventures and entrepreneurial culture can be a valuable solution for fostering entrepreneurial thinking and youth employment. Therefore, the aim of this article is to investigate the influence of entrepreneurial management and entrepreneurial competencies, mediated by entrepreneurial behavior, in small and medium-sized enterprises. Methods: The current research is considered exploratory in terms of purpose and applied in nature, employing a descriptive-correlational methodology. The population of this study consists of employees and managers of small and medium-sized enterprises in Tehran. Utilizing Cochran’s formula for an unknown population, a sample size of 384 individuals was determined. Non-probability convenience sampling was employed in this study. Data collection was conducted through a questionnaire. Findings: The results indicate that the influence of entrepreneurial management and entrepreneurial behavior on entrepreneurial competence in small and medium-sized enterprises is significant. Additionally, entrepreneurial management and entrepreneurial behavior, mediated by entrepreneurial behavior, have a positive and significant impact on entrepreneurial competence. Conclusion: Thus, according to the findings of the conducted research, there is evidence of significant and positive effects of entrepreneurial management and entrepreneurial behavior on entrepreneurial competence in SMEs.